THE EFFECT OF READING HABIT AND VOCABULARY MASTERY TOWARDS STUDENTS’ READING COMPREHENSION (Survey at State Senior High School in Central Jakarta) - Retno Rahayuningsih (Wanastra: Jurnal Bahasa dan Sastra, 2020)
This research is a kind of survey and aims to find out and analyze empirically the effect of reading habit and vocabulary mastery towards student’s reading comprehension. The observed population of this research in state senior high school students in Central Jakarta. The sample was gained through simple random sampling. The gained data was then analyzed by using correlation technique and multiple regressions. Previously, the prerequisite tests before examining the regression test must be accomplished, such as normality test and linearity test. The result of this research is there are any significant effects of reading habit and vocabulary mastery altogether towards students’ reading comprehension at State Senior High School in Central Jakarta